IMPLEMENTATION OF THE WASPAS METHOD FOR DETERMINING THE QUALITY OF WOOD TYPES OF FURNITURE MATERIALS - Swastika, Rulin; Rahman, Efi; Anjani, Cindy Vernica (Institut Bakti Nusantara, 2023)
After Brazil, Indonesia have forest Rain tropical biggest second, and have diversity rich life, incl wood quality tall. Component the main thing really influence caliber furniture or craft wood other is wood. So from that is, create an election program quality wood best For material Furniture with use Draft System Supporter decision. The method that will be used in study This adalan WASPAS method. In collecting data using method literature study, observation, interviews with gather a number of criteria and alternatives. There are five criteria used that is texture strong materials, minimal maintenance, no easy burn, hold on to pest, no Lots absorb water. For alternative taken there are five types wood, that is wood teak, albizia, medang, cempaka, and mahogany. Alternative Test Results obtained, the wood is considered worthy and possessing quality best for material standard Mebelar is Cempaka with calculation results with a value of 92.25.